DEVELOPMENT AND VALIDATION OF HPLC-DAD METHOD FOR THE DETERMINATION OF BISOPROLOL IN TABLET DOSAGE FORMS - Kondratova, Yuliya; Logoyda, Liliya; Voloshko, Yuliia; Abdel-Megied, Ahmed; Korobko, Dmytro; Soroka, Yuriy (International Journal of Applied Pharmaceutics, 2017)
Objective: A rapid, simple and sensitive RP-HPLC method was developed and validated for the determination of bisoprolol fumarate in bulk and pharmaceutical dosage form. Methods: Chromatographic separation was achieved within 2.5 min on ACQUITY Arc System, Waters Symmetry C18 column (3.9 mm i.d. X 150 mm, 5 Î¼m particle sizes) using a mobile phase consisted of acetonitrile: phosphate buffer (25:75 v/v) in an isocratic mode at a flow rate of 1.4 ml/min. The pH of the mobile phase was adjusted to 7.0 with orthophosphoric acid and UV detection was set at 226 nm. Results: The retention time for bisoprolol fumarate was found to be 2.09 min. The proposed method was validated according to ICH guidelines with respect to linearity, specificity precision, accuracy and robustness. The limit of detection and limit of quantification are calculated and found to be 0.4825 and 1.4621 Î¼g/ml; respectively. Conclusion: The proposed method can help research studies, quality control and routine analysis with lesser resources available. The results of the assay of pharmaceutical formulation of the developed method are highly reliable and reproducible and is in good agreement with the label claim of the medicines.